Contestability and Changes in Tolerance towards Corruption : The Formation of an Elite-Citizen Coalition in Mexico - Lach, Samantha (World Bank, Washington, DC, 2017)
This paper uses some of the main elements of the World Development Report 2017 framework to analyze how the initiative came to be. First, it looks to investigate the origin of the constitutional changes that gave birth to the figure of citizen’s bill in the first place, illustrating how a change in rules, a “form”, eventually led to an increased space of contestability. It also looks to document how the coalition between civil society organizations, academia, the private sector and citizens came together around this rallying point, and how the bill grew from online platform to a full-on legislative proposal. Afterwards, it provides a brief analysis of the elements of the bill that were ultimately incorporated into the legislation of the national anticorruption system. In parallel, it looks to shed light on questions, such as, did political parties attempt to block a constitutional change with the potential to affect their interests? What role did elite organizations play in the civil society coalition? How much of the coalition’s bill made it into the national anticorruption legislation? What are the mechanisms through which these laws purpose to fight corruption? The methodological approach followed in the paper consisted of in-depth interviews with key stakeholders and a detailed review of publicly available information. The rest of the paper is structured as follows. Section two, next, discusses some of the elements of WDR 2017, which are used to frame the analysis. It then sets up the context leading up to the initiative, notably the legislative changes that allowed the figure of citizen’s bill to come to the fore. Section three looks at the path of the 3de3 citizen’s bill: its evolution from online platform, through massive crowdsourcing to full-blown national anticorruption bill. It also explores some of the most distinctive elements that the bill proposes to fight corruption. Section four provides an analysis of the incentives behind how the coalition around the initiate was built, and the unlikely alliance of actors involved—citizens, business associations, civil society organizations, academia, and legislators themselves. Section five concludes with a discussion of the entry points that led to the development of the bill—and its incorporation into the national legislation on corruption—in terms of shifts in incentives, preferences and contestability.